African American children in early childhood education : making the case for policy investments in families, schools, and communities - Iruka, Iheoma U.; Curenton, Stephanie M.; Durden, Tonia R. (Emerald Publishing, 2017)
This book presents both the challenges and opportunities that exist for addressing the critical needs of black children, who have been historically underserved in the U.S. education system, exploring the language, cognitive, social-emotional, and health development of children from birth to age 8.
Keywords: African Americans -- Education (Early childhood); elektronické knihy; electronic books